The Fake Diary of a Historical Figure: Klementyna Tańska-Hoffmanowa’s Journal of Countess Françoise Krasińska (1825) - Magdalena Ożarska (Theatrum Historiae)
This paper discusses a somewhat forgotten diary novel by the first Polish woman writer and educator to make a living from creative writing, Klementyna Tańska-Hoffmanowa (1798–1845). The Journal of Countess Françoise Krasińska (1825) was one of her early works, designed for adolescent readers (first serialised in Rozrywki [Amusements], a youth magazine which she had started but a year earlier). Françoise (Polish: Franciszka) Krasińska was a historical character: born into a Polish aristocratic family of the Corvin-Krasińskis in 1742, she set her mind on rising above the social station originally allocated to her. Around fifteen, she met Royal Prince Charles (Karl) Christian Joseph of Saxony. They were secretly married on March 25, 1760. This morganatic marriage spelled years of solitude, financial straits and emotional imbalance for Krasińska. The spouses were not to be reunited until over a decade after the wedding. The long separation was largely due to the character of the Prince, who had hoped to become King of Poland, which however never materialised. They had only one daughter, Princess Maria Christina of Saxony, who in due course became the grandmother of Victor Emanuel II, the first king of united Italy. Hoffmanowa’s novel, begun as a project aimed to educate young girls in modesty and other traditional feminine virtues, soon became a tour-de-force of fake diarising, the first ever psychologically complex presentation of the workings of a young girl’s mind in Polish literature. The diary was rendered so convincingly that it was for decades taken as a transcript of a real journal (hence its several translations into Western languages). Yet it is now quite clear that the novelist produced her manuscript on the basis of genuine correspondence of Françoise Krasińska, to which she had unrestricted access, and historical newspaper accounts, but not a journal as it had never existed. In my paper, I wish to discuss the Journal’s precarious balance between historical fact and fiction as well as examining the ways in which this autobiographical forgery is enacted.